2017
DOI: 10.4025/actascianimsci.v39i4.34426
|View full text |Cite
|
Sign up to set email alerts
|

<b>Aerobic stability in corn silage (<i>Zea mays</i>L.) ensiled with different microbial additives

Abstract: ABSTRACT. This study aimed to assess different microbial additives, regarding the efficiency of aerobic stability in corn silages. The corn hybrid used for silages production was the DKB 310. . The experimental design was completely randomized with five replicates for each treatment. For the parameters evaluated daily, we used the split plot design, in which the different silages were assigned to the plots and the time of exposure to air was assigned to the subplots. There was no difference of additives on sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Silva et al [ 26 ] used L. buchneri strains and noted an increase in the CP level compared with that in the control sample. Similar results were reported by Bumbieris et al [ 27 ], who observed that the CP content in inoculated samples (7.47%) was greater than in the control samples (6.87%). Lactobacillus strains used in our study reduced yeast and mould counts.…”
Section: Discussionsupporting
confidence: 91%
“…Silva et al [ 26 ] used L. buchneri strains and noted an increase in the CP level compared with that in the control sample. Similar results were reported by Bumbieris et al [ 27 ], who observed that the CP content in inoculated samples (7.47%) was greater than in the control samples (6.87%). Lactobacillus strains used in our study reduced yeast and mould counts.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, researchers have confirmed that B. subtilis can produce antifungal and antibacterial substances, that can inhibit the growth of undesirable microorganisms such as yeast and filamentous fungi, and prevent silage spoilage and mycotoxin production ( Bonaldi et al, 2021 ), which may be applicable to improving aerobic stability. Inoculation with B. subtilis can improve the aerobic stability of silage ( Bumbieris et al, 2017 ; Bai et al, 2020 ), but studies on its role in whole plant corn silage are inadequate. Gandra et al (2017) observed that co-inoculation of L. buchneri and B. subtilis improved the aerobic stability of sunflower silage by reducing the number of aerobic and spoilage microorganisms and increasing the number of lactic acid bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…However, the temperatures of I and L increased linearly over time after opening of silo. The increase in temperature over time is because of the enzymatic activity of the deleterious microorganisms that release energy (heat) during the process of nutrient degradation (Bumbieris Junior et al, 2017). This is different from what occurs normally in corn silages (Tomaz et al, 2018) and supports the concept that tropical grasses are more prone to deterioration by aerobic bacteria.…”
Section: Resultsmentioning
confidence: 92%
“…As a consequence, microbial metabolic activity inside the silo is reduced and the forage can be preserved for longer periods (McDonald et al, 1991). High pH conditions also favour development of Clostridium bacteria, which can take advantage of aerobic conditions after opening the silo to convert proteins into NH 3 -N (Bumbieris Junior et al, 2017;Zanine et al, 2018). Controlling Clostridium bacteria in silages with inoculants can be difficult in humid conditions, and dry matter may be lost as a result (Tomaz et al, 2018).…”
Section: Resultsmentioning
confidence: 99%